2009
DOI: 10.1123/tsp.23.2.170
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Flow: A Qualitative Study of Dependence in Big Wave Surfing

Abstract: (2009) The dark side of flow: a qualitative study on dependence in big wave surfing. Sports Psychologist, 23 (2). pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 22 publications
(39 reference statements)
0
47
1
3
Order By: Relevance
“…Only researchs on white-water canoeists (Sparkes & Partington, 2003) or big-wave surfers (Partington, Partington, & Olivier, 2009) have analyzed flow in conditions in which the athlete does not have control over the task or in which the requirement level of the task exceeds his/her ability. In the context of studies of firefighters, it is worth highlighting Chen-Lin's recent work (2014), which concludes that flow state has a positive influence on work satisfaction in volunteer firefighters.…”
Section: Introductionmentioning
confidence: 99%
“…Only researchs on white-water canoeists (Sparkes & Partington, 2003) or big-wave surfers (Partington, Partington, & Olivier, 2009) have analyzed flow in conditions in which the athlete does not have control over the task or in which the requirement level of the task exceeds his/her ability. In the context of studies of firefighters, it is worth highlighting Chen-Lin's recent work (2014), which concludes that flow state has a positive influence on work satisfaction in volunteer firefighters.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, Farmer (1992) found that vertigo, which may include feelings of self-transcendence or loss of self, was the main motivating factor for surfing. Partington et al (2009) found that big wave surfers craved the flow states they experienced, which include a heightened sense of focus and self-awareness.…”
Section: Surfing and Spiritualitymentioning
confidence: 99%
“…During a flow state, the individual is said to be living completely in the moment and has a narrowed, intense focus on the activity at hand (Csikszentmihalyi, 1975). Partington et al (2009) investigated the flow experiences of "big wave" surfers and found that they reported improved mood states, better surfing performance, and higher self-esteem and fulfillment as a result of these experiences. Surfers also reported an "addiction" to these feelings which led to their continued involvement in big wave surfing regardless of family commitments, potential injuries, or even potential death (Partington, et al, 2009).…”
Section: Psychological Correlates Of Surfingmentioning
confidence: 99%
See 2 more Smart Citations